ACCURACY OF RECALL FOR MANIA SYMPTOMS USING A THREE MONTH TIMELINE FOLLOW-BACK INTERVIEW - Simon, Gregory E (2007)
OBJECTIVE: Little research has examined the accuracy of recall for mood symptoms using retrospective timelines or life charts. We examined accuracy of recall for mania symptoms over a period of 3 months. METHODS: Data were collected from a sample of 392 patients enrolled in a randomized trial of a psychoeducation and care management program for bipolar disorder. Every three months, participants completed in-person assessments including the Longitudinal Interval Follow-Up Examination, a timeline follow-back interview assessing mood symptoms during each week since the previous assessment. Brief telephone assessments of mood symptom severity were performed at a randomly selected point between in-person interviews. Mania symptoms recalled at the in-person assessment were compared to those reported in the previous telephone interview. RESULTS: The proportions of weeks with full or subthreshold mania symptoms recalled at the in-person interview were similar to those detected by telephone assessments. When compared to telephone assessments, sensitivity of recall for detecting subthreshold or greater symptoms of mania was 63% (95% CI 57% to 69%). Specificity for detecting absence of significant mania symptoms was 76% (95% CI 71% to 80%). LIMITATIONS: Validation of recall was based on brief telephone assessments rather than detailed in-person interviews. Our results may not apply to recall over longer time periods. CONCLUSIONS: A timeline follow-back interview demonstrated acceptable sensitivity and specificity for detecting symptoms of mania during a specific week in the prior three months.